Integrated Cuckoo-Evolutionary Programming-Based Technique Incorporating Distribution Generation for Economic Dispatch in Power System - Ahmad Nazri, Ahmad Faris Hakim; Zulkefle, Habibah; Musirin, Ismail; Ismail, Nor Laili; Abdul Halim, Mazliza; Mohamed Kamari, Nor Azwan; Abdullah, Azlina; Kasinathan, Vinothini; Mustapha, Aida (International Journal of Integrated Engineering, 2025)
In electricity generation, optimizing operational costs remains a primary concern for power systems. Economic Dispatch (ED) has been extensively explored in the power system domain; however, the impact of compensating devices, such as Distributed Generation (DG), has not been thoroughly investigated and requires further study to enhance system efficiency. This paper introduces an integrated cuckoo-evolutionary programming-based technique, referred to as CSA-EP, which incorporates DG into the ED problem. The CSA-EP technique combines the Cuckoo Search Algorithm (CSA) with Evolutionary Programming (EP) to optimize generation costs. The proposed method aims to identify the optimal power output for all generators in the system, minimizing overall generation costs. The proposed system was tested on the IEEE 30-Bus Reliability Test System (RTS) in solving the ED problem. In comparison to CSA and EP, the CSA-EP optimization technique demonstrated superior performance. Specifically, CSA-EP achieved a minimized cost of $2649.4932 per hour under base case conditions, whereas CSA alone yielded $5167.0848 per hour, and EP resulted in $3010.9971 per hour. In Case 1, IC-EP further demonstrated its effectiveness by achieving a minimized cost of $2649.4932 per hour, in contrast to $5529.7107 per hour for CSA and $4209.5214 per hour for EP. These results underscore the superior efficacy of the CSA-EP approach in minimizing generation costs.